BALALARDA DÓRETIWShILIKTI RAWAJLANDÍRÍWDA M.MONTESSORI METODLARÍNAN PAYDALANÍW - Xudaybergenova, G. (SCIENCE and SOCIETY, 2025)
The article examines the main provisions of using M. Montessori’s methodology in developing creative abilities in preschool children, the principles of a child-friendly approach in Montessori schools and classes.